Factors Influencing Social Entrepreneurial Intention: A Case of Private University in Bekasi - Anggraeni Permatasari; Garry Doohan; Muhammad Setiawan Kusmulyono (Faculty of Business, President University, 2020)
This research analyses the influence of emotional intelligence, self-efficacy, attitude, and subjective norms towards social entrepreneurial intention in University students. Quantitative research was chosen to conduct this research. Two hundred five respondents responded were participated in this research. Multiple Regression analysis was utilized as a statistical tool analysis to test the hypothesis. This study found a significant influence between emotional intelligence, self-efficacy, attitude, and subjective norms towards social entrepreneurial intention (simultaneously). This research also defines which factors influence students to engage on social entrepreneurship projects in the context of private university.